Bioecological profiles of preschool children’s individual, familial, and educational characteristics, and their relations with school adjustment, academic performance, and executive function in first grade - Lee, Young-Eun (Frontiers in Psychology, 2023)
This study investigates the relationships between distinct bioecological profiles of individual, familial, and educational characteristics of preschool children and their school adjustment, academic performance, and executive function in first grade. Data on 11 indicators of personal and environmental characteristics were collected from 1,016 five-year-old Korean preschoolers using a national-level open dataset. Latent profile analysis identified five profiles that were associated with different levels of school adjustment, academic performance, and executive function one year later when the preschoolers became first graders. The “Good Social Competence by Good Familial Environment” profile was the most associated with levels of school adjustment, academic performance, and executive function. The “Good Social Competence by Good Educational Environment” profile was more associated with levels of school adjustment and executive function than the “Moderate” profile but less associated with these levels than the “Good Social Competence by Good Familial Environment” profile. Findings indicate that the environment, rather than individual characteristics of preschoolers, plays a more significant role in their elementary school adjustment, academic performance, and executive function, and that their familial environment plays a more significant role than their educational environment. The study highlights the importance of creating supportive familial environments for preschool children to improve their school adjustment, academic performance, and executive function in elementary school, and provides a useful guide for practitioners and policymakers seeking to improve children’s academic and socioemotional outcomes.